Synthesizing the Influence of Country of Origin on Consumer Buying Behavior - Aggarwal, Shivani; Jain, Dr. Vipul (The journal of contemporary issues in business and government, 2023)
The particular research paper incorporates with country of origin effects on consumer behavior. It is a review of various researches that has already been conducted in this field over the years. It provides us with the long discussed answer that the country of origin does effect consumer beliefs, perceptions and attitudes. Country’s image effect and the possibility of consumer to be ethnocentric, leads into certain biasness for particular products of specific countries, which eventually neutralizes as consumer get involved in their purchases and get to know more about the product. The differences in consumers, based on demographic profile also acts as a factor into varying degree of country of origin effects. The study constitutes of important information for the marketers, who are often in dilemma about the strategy to be adopted for the customers. As because, even though the world is globalized, it still is running carrying in itself various boundaries such as cultural, political and economic environment.